APPLICATION OF ENGINEERING MANAGEMENT IN DEVELOPING THE LOCAL FOOD INDUSTRY SPICE COFFEE - Endra Yuafanedi Arifianto (Agroindustrial Technology Journal, 2023)
The micro-scale food industry has a significant role in maintaining regional economic stability during a pandemic. The ability of food industry players to take advantage of community needs and the availability of natural resources is the key to growing business in this sector. One of the micro-scale food industries that has been able to grow during the pandemic and is mushrooming in several regions today is the spice coffee industry. Changes in the business model took place very quickly during the pandemic to support the availability of food, especially herbal products. Society needs coffee spices as an alternative supplement to help the immune system. This study uses an engineering management approach in explaining the concept of developing a local spice coffee food business. The results of applied engineering management include marketing research, business management engineering, and digital technology. Advances in digital technology, limited conditions of direct interaction, easy access to information, and high demand in the market have forced the spice coffee food industry to collaborate with various parties in developing new business models. Keywords: food industry, spice coffee, engineering management, digital technology, food